The Use of Augmented Reality Cards to Improve Science Learning Outcomes About the Effect of Force on The Shape and Motion of Objects - Ratna Ningsih, Inge Nur Indah Sri Rejeki (Journal of Education Technology, 2020)
The Science Learning of Kepanjen II Elementary School, Kecamatan Jombang, in the fourth grade on the effect of force on the shape and direction of motion of objects, experienced problems in the form of difficulty understanding the material by students. The results of the learning evaluation show that only 55% of the 30 students scored above the predetermined KKM of 75.0. Based on the problems that occur, the researchers plan to improve learning in 2 cycles. At the planning stage, it is carried out by analyzing KI and KD, making indicators, learning objectives, and continuing with compiling a lesson plan implementation and developing learning assessment instruments. Finally, in the planning stage, it is to create learning media, the Augmented reality application. At the implementation stage of learning has increased both teacher activities and student activities. Overall, the increase in teacher activity increased from 70% to 80%. Meanwhile, student activity increased from 72% to 90%. Learning outcomes before using Augmented Reality card media classical completeness of 55%. The results of student learning in the first cycle of classical completeness of 63% and the second cycle has increased to 84%.